Regimes of participation: theorising participatory archives from the outset of archivists' views on archival institutions and user participation in Scandinavia - Isto Huvila (Information Research: An International Electronic Journal)
Introduction: In spite of the prominence of the notion of participatory archives, there is no consensus of what participation entails in archival contexts and a lack of theory to explain the mechanisms underpinning the diversity of views.